UJI DAYA HAMBAT SALEP EKSTRAK ETANOL DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb.) TERHADAP BAKTERI Staphylococcus aureus - Maulana Zulkarnain Imansyah (Akademi Farmasi Yamasi Makassar, 2022)
Research has been carried out to test the inhibitory power of the ethanol extract of pandan leaves (Pandanus amaryllifolius Roxb.) ointment against Staphylococcus aureus bacteria. The aim of this study was to determine the inhibition of the ointment preparation of ethanol extract of fragrant pandan leaves (Pandanus amaryllifolius Roxb.) against Staphylococcus aureus bacteria. First, fragrant pandan leaves are made into simplicia and then extracted with 96% ethanol solvent, then the extract obtained is made into an ointment with an extract concentration of 10% and 20%, where the ointment base used is vaselinum and adeps lanae base, then the ointment is tested for effects. its inhibition against Staphylococcus aureus bacteria using the well method and incubated for 1 × 24 hours. The average diameter of the inhibition obtained from the sample preparation of the ethanol extract of pandan fragrant leaf ethanol extract with a concentration of 10%: 0 mm, 20%: 8.3 mm, and the positive control used was gentamicin with an average inhibition zone of 10.6 mm